Determinación de plazos en las diligencias procesales del delito de violencia Psicológica para evitar vulneración de derechos - Guzman Riofrio, David Santiago (2018)
The present legal investigation deals with the "Determination of deadlines in the procedural proceedings of the crime of psychological violence to avoid violation of rightQs." Interest arises to develop it due to the existence of a social problem related to psychological violence; verified through a detailed study, verifying records in file processing and evidencing the imperative need to find a viable solution so that the psychological assessment and the respective expert report are prepared in order to become a probative element in the criminal process . Similarly, facilitating action by the administration of justice by preventing the violation of rights and checking whether the legal treatment given to psychological violence against women or members of the family meets and guarantees the Constitutional Rights of the victim of violence established in article sixty-six numeral three, literal b, of the Constitution of the Republic of Ecuador; that, briefly guarantees: "A life free of violence in the public and private sphere." Constituted in a Constitutional obligation for the State to implement necessary measures as provided for in the Convention Belém Do Pará signed and ratified by Ecuador that establish the obligation of States parties to guarantee access to justice mechanisms and fair and effective comprehensive reparation.